Genome-Wide Expression and Physiological Profiling of Pearl Millet Genotype Reveal the Biological Pathways and Various Gene Clusters Underlying Salt Resistance - Awan, Samrah Afzal; Khan, Imran; Tariq, Rezwan; Rizwan, Muhammad; Wang, Xiaoshan; Zhang, Xinquan; Huang, Linkai (Frontiers in Plant Science, 2022)
Pearl millet (Pennisetum glaucum L.) is a vital staple food and an important cereal crop used as food, feed, and forage. It can withstand heat and drought due to the presence of some unique genes; however, the mechanism of salt stress has been missing in pearl millet until now. Therefore, we conducted a comparative transcriptome profiling to reveal the differentially expressed transcripts (DETs) associated with salt stress in pearl millet at different time points, such as 1, 3, and 7 h, of salt treatment. The physiological results suggested that salt stress significantly increased proline, malondialdehyde (MDA) content, and hydrogen peroxide (H2O2) in pearl millet at 1, 3, and 7 h of salt treatment. In addition, pearl millet plants regulated the activities of superoxide dismutase, catalase, and peroxidase to lessen the impact of salinity. The transcriptomic results depicted that salt stress upregulated and downregulated the expression of various transcripts involved in different metabolic functions. At 1 and 7 h of salt treatment, most of the transcripts were highly upregulated as compared to the 3 h treatment. Moreover, among commonly enriched Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, the mitogen-activated protein kinase (MAPK) signaling pathway and peroxisome pathway were significantly enriched. The DETs related to hormone signaling (auxins, ethylene, gibberellin, and abscisic acid), kinases, protein modifications, and degradation were also identified, depicting the possible role of hormones and kinases to enhance plant tolerance against salt stress. Furthermore, the transcription factors, such as ethylene-responsive element binding factors (ERF), basic helix-loop-helix (bHLH), HMG box-containing protein (HBP), MADS, myeloblastosis (MYB), and WRKY, were predicted to significantly regulate different transcripts involved in salt stress responses at three different time points. Overall, this study will provide new insights to better understand the salt stress regulation mechanisms in pearl millet to improve its resistance against salinity and to identify new transcripts that control these mechanisms in other cereals.